Adult characteristics of survivors of early life malnutrition in an impoverished population. Issue 8 (August 2020) - Muthuuri, J.M.; Some, Eliab Seroney; Chege, Peter
Summary: Background & aims: To determine the characteristics of adults who survived early life malnutrition (ELM) and the possible associated factors. The setting is an impoverished community in Kenya. The coastal region of Kenya has a high prevalence of acute protein-energy-malnutrition and stunting. Methods: Observational cross-sectional survey where 872 skeletally mature adults of African origin, were surveyed in a period of three months. A discrimination tool to detect ELM survivors was created. Personal, historical and family data were collected in a semi-structured questionnaire. Various observations and body measurements were done. The subjects were grouped into two, those with ELM (Group1), and those without (Group2). Results: Group1 had 242 participants, 49.8% males, mean age of 49.1 ± 8.7 years. Group2 had 630 participants, 48.3% males, mean age 41.0 ± 9.7 years. The phenotypic characteristics included height, BMI, and head circumference (P < 0.05). Developmental characteristics were duration of schooling, occupation and income (P < 0.001). Factors associated with malnutrition were County of origin, parental education, parental occupation, and family size (P < 0.001). Conclusions: There are discernible phenotypic and developmental characteristics associated with adult survivors of ELM. The predisposing factors for ELM are location of birth, parental education and occupation, and family size.